A Comparative Analysis of Resilience of Islamic and Conventional Banks in Indonesia - Ulina, Sri; Majid, M. Shabri Abd. (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
The presence of the 2008 Global Financial Crisis (GFC) has adversely impacted both conventional andÂ Islamic banking performances. This study aims to empirically compare the ï¬nancial performances betweenÂ Islamic banks and conventional banks during the pre- and post-2008 GFC periods. It also attempts toÂ compare the ï¬nancial performance of each Islamic and conventional bank between the pre- and post-2008Â GFC periods. Three state-owned banks from each conventional and Islamic banking category were selectedÂ as the study sample using the purposive sampling technique. Based on the independent sample t-test, theÂ study found a signiï¬cant diï¬€erence between the Islamic and conventional banking performances during theÂ pre- and post-2008 GFC periods. Meanwhile, based on the paired t-test, the decline in Islamic bankingÂ performance from the pre-2008 GFC to the post-2008 GFC periods was signiï¬cantly smaller than theirÂ conventional banking counterparts. These ï¬ndings show the Islamic banks' superiority over theirÂ conventional banking counterparts due to fair and just practices based on Islamic tenets. Due to theirreliance in facing the episodes of crises, the Islamic banks deserve a strong support by government byÂ enhancing prudent Islamic banking regulation. The Islamic banks should strive to operate fully based on theÂ shari'ah principles and prudent banking management.